Biosensing: Tunable Fano‐Resonant Metasurfaces on a Disposable Plastic‐Template for Multimodal and Multiplex Biosensing (Adv. Mater. 19/2020). Issue 19 (11th May 2020) - Ahmed, Rajib; Ozen, Mehmet Ozgun; Karaaslan, Merve Goksin; Prator, Cecilia A.; Thanh, Cassandra; Kumar, Shreya; Torres, Leonel; Iyer, Nikita; Munter, Sadie; Southern, Sarka; Henrich, Timothy J.; Inci, Fatih; et al.
Abstract : Metasurface fabrication techniques are costly and time consuming since they require multiple complex deposition and patterning steps to build devices with only a small active area. Digital versatile disks (DVDs) are commonly available and are used to play movies. In article number 1907160, Fatih Inci, Utkan Demirci, and co‐workers utilize these DVDs to create a plastic‐templated metasurface allowing the fabrication of cost‐effective Fano‐resonant biosensors over a large active area with layer‐by‐layer bio‐sensing of binding intact viruses, i.e., HIV, proteins, and antibodies. Image credit: M. Giray Ögüt.